2013
DOI: 10.1111/dme.12348
|View full text |Cite
|
Sign up to set email alerts
|

‘Cough‐triggered’ tuberculosis screening among adults with diabetes in Tanzania

Abstract: Aims Diabetes increases the risk of tuberculosis and the prevalence of diabetes is rising in tuberculosis-endemic regions such as sub-Saharan Africa. Resource-appropriate strategies for tuberculosis case finding among African adults with diabetes are needed. The aims of this study were to determine prevalence of tuberculosis and evaluate one screening strategy among adult Tanzanians with diabetes. Methods In this prospective cohort study, we evaluated a “cough-triggered” strategy for tuberculosis case findin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
3
12
0
Order By: Relevance
“…The prevalence rate of active TB in our study was within the range of 0.1–6.2%; reported prevalence rates from previous screening studies conducted in similar high TB burden settings such as Tanzania and Ethiopia [16] , [17] . However, our study differs from many others in that all DM patients were screened for active TB irrespective of reported symptoms.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The prevalence rate of active TB in our study was within the range of 0.1–6.2%; reported prevalence rates from previous screening studies conducted in similar high TB burden settings such as Tanzania and Ethiopia [16] , [17] . However, our study differs from many others in that all DM patients were screened for active TB irrespective of reported symptoms.…”
Section: Discussionsupporting
confidence: 69%
“…However, our study differs from many others in that all DM patients were screened for active TB irrespective of reported symptoms. In similar screening studies, sputum samples were collected from only DM patients clinically suspected of having TB [15] , [16] , [30] . Previous evidence has shown that symptom screening may not be an effective method in detecting TB in those with HIV [31] , [32] and DM [33] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The few studies that have been performed show varying prevalence of DM in TB patients, ranging from 3% [12] to 36% [13], more than 5 folds greater than in the general population [14,15]. In Tanzania, 1.3% of screened adults with DM had TB, 7–fold greater than the general population [16]. A review of 13 observational studies, of which only one was from a low-income country and none from Africa, found that diabetes was associated with TB regardless of study design [17].…”
Section: Introductionmentioning
confidence: 99%
“…Extrapolation is difficult, but we expect rates of TB disease among symptomatic patients in this South African study to resemble those in similar sub-Saharan countries such as Tanzania (7.4%) or Botswana (13.9%). 20,34…”
Section: Discussionmentioning
confidence: 99%